Predictors of response to opicinumab in acute optic neuritis - Cadavid, Diego; Balcer, Laura; Galetta, Steven; Aktas, Orhan; Ziemssen, Tjalf; Vanopdenbosch, Ludo J; Leocani, Letizia; Freedman, Mark S; Plant, Gordon T; Preiningerova, Jana Lizrova; Ziemssen, Focke; Massacesi, Luca; et al. (Annals of clinical and translational neurology, 2018)
OBJECTIVE: The objective of this study was to evaluate prespecified and post hoc analyses in RENEW subgroups to identify participants more likely to benefit from opicinumab. METHODS: RENEW assessed the efficacy/safety of opicinumab versus placebo in participants with a first unilateral acute optic neuritis (AON) episode. Difference in visual evoked potential (VEP) latency of the affected eye at 24 weeks versus the fellow eye at baseline was the primary endpoint. Interactions between the primary endpoint and prespecified baseline variables (including age, timing of treatment initiation, and visual impairment) using the median as cut-off were evaluated in the per protocol population using analysis of covariance (ANCOVA); subgroups based on preexisting brain T2 lesion volume were also analyzed. Interactions between the primary endpoint and retinal ganglion cell layer/inner plexiform layer (RGCL/IPL) and retinal nerve fiber layer (RNFL) thickness were assessed post hoc as was weight gain by treatment. RESULTS: Treatment benefit of opicinumab (n = 33) over placebo (n = 36) on the primary endpoint was greatest in participants older than the median age at baseline (≥33 years); the difference versus placebo for baseline age ≥33 years was -14.17 msec [P = 0.01] versus -0.89 msec for baseline age <33 years, [P = 0.87]). Post hoc analysis showed that VEP latency recovery was significantly associated with less RGCL/IPL thinning (P = 0.0164), occurring early on. INTERPRETATION: Age was the strongest prespecified baseline characteristic associated with a treatment effect of opicinumab. A strong association between VEP latency recovery at week 24 and early RGCL/IPL preservation was observed.